2019
DOI: 10.1111/jocn.15107
|View full text |Cite
|
Sign up to set email alerts
|

A courageous journey: Experiences of migrant Philippine nurses in Norway

Abstract: What does this paper contribute to the wider global clinical community?  Attention should be paid to the integration of immigrant nurses to safeguard and strengthen their professional competencies and prevent discrimination in the job market.  There is a need to facilitate effective language training as well as well-founded and predictable systems of credentialing for Philippine nurses and other IENs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 36 publications
(44 reference statements)
4
37
0
1
Order By: Relevance
“…Eriksson et al, 2018;Moyce et al, 2016;Wheeler et al, 2014). Even though language tests assess basic language competency, they do not address the communication needs of a nurse (Ghazal et al, 2019), which might explain the language difficulties described in the present study and several others (Chun Tie et al, 2019;Eriksson et al, 2018;Lum et al, 2016;Nortvedt et al, 2020;Stubbs, 2017;Viken et al, 2018). Some IENs in our study expressed the need for additional courses, both in language and in preparation for the examinations.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Eriksson et al, 2018;Moyce et al, 2016;Wheeler et al, 2014). Even though language tests assess basic language competency, they do not address the communication needs of a nurse (Ghazal et al, 2019), which might explain the language difficulties described in the present study and several others (Chun Tie et al, 2019;Eriksson et al, 2018;Lum et al, 2016;Nortvedt et al, 2020;Stubbs, 2017;Viken et al, 2018). Some IENs in our study expressed the need for additional courses, both in language and in preparation for the examinations.…”
Section: Discussionmentioning
confidence: 57%
“…Despite the various methods of recertification used across the globe, research from around the world has described the recertification process as long and challenging (Chun Tie et al, 2019;Covell et al, 2016;Eriksson et al, 2018;Nortvedt et al, 2020;Salami et al, 2018). The process has been described as financially burdensome and unfair (Nortvedt et al, 2020) as well as difficult to understand (Eriksson et al, 2018;Salami et al, 2018), and the nursing and language exams have been described as challenging (Covell et al, 2016;Eriksson et al, 2018;Salami et al, 2018). Although individual informal support and formal educational resources can help IENs prepare for nursing exams (Covell et al, 2017), IENs have reported a lack of support during the process (Salami et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, clinical training at these institutions is not part of the Philippine nursing education curriculum, and it may explain the contrast between the nurses’ training environments and the nursing context encountered in host countries in the Western world. A more structured transition program that focuses on elderly care would be beneficial, particularly for the Filipino nurses that work as auxiliary nurses while waiting for RN authorization (Fagertun & Tingvold, 2018; Nortvedt et al, 2020). The majority are recruited to work in community health services, and institutions, such as nursing homes or home care services, often rely on immigrant nurses (Klaus, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Western nursing is dominated by whiteness 1 and femininity, overshadowing subaltern voices and silencing ontologies and epistemologies that do not abide by Western Eurocentric norms. This contributes to processes of “Othering” (Krabbe, 2021 ; Santos, 2018 ) that perpetuate racism and other forms of discrimination within nursing, particularly against nurses of color, and by nurses toward others, including patients (Jenkins & Huntington, 2015 ; Metzger et al, 2020 ; Neiterman & Bourgeault, 2015 ; Nortvedt et al, 2020 ; Tie et al, 2018 ; Truitt & Snyder, 2020 ; Walani, 2015 ). In turn, these ideological stances have problematic consequences in nursing discourse, clinical practice, education, research, and leadership.…”
Section: Introductionmentioning
confidence: 99%